Emergency Education as a Catalyst for Teacher Change: Extent and Correlates of the Class and Subject Teachers' Growth of Competences - Katarina Z. Mićić; Selena N. Vračar (University of Belgrade, Teacher Education Faculty, 2023)
The aim of this study was to explore the possibility that the emergency education during the Covid-19 pandemic served as a catalyst for teacher development. We investigated the growth of teachers' competences that were highlighted by the online teaching, and looked into personal and school factors that stimulated or restricted this growth. Four domains of expected teacher growth were chosen: general digital competence, pedagogical-digital competence, competence for student assessment, and competence for conducting inclusive practices. A total of 314 teachers filled out an online questionnaire and rated their pre-pandemic and current levels of 18 items describing skills, beliefs, and attitudes of the four selected domains. The instrument also included scales for measuring school-related (leadership, teacher autonomy, collaboration) and teacher-related variables (teacher self-efficacy, growth mindset, reflective practice). The results of the paired samples t-test showed that improvements of the competences were significant in all four domains, and the highest in the domain of pedagogical-digital competence. Partial correlations revealed that teacher-level variables were more important factors of the growth than school-related variables. Differences between the class and subject teachers were found. Recommendations are given in the direction of supporting the emerged good practices and maintaining of the developed competences in the post-pandemic era.